American political values and agency theory: A perspective - Kaen, Fred R. (Journal of business ethics, 1988)
This paper explores the historical American political values which have shaped modern financial theory and agency theory. Financial agency theory's intellectual roots are shown to be located in the liberal tradition which espouses the instrumental nature of property and property rights. The paper also argues that financial theorists should recognize that, historically, economic efficiency was not a value or end in itself but merely a means by which more fundamental social goals might be achieved.